Shunt nephritis - Viviana Parra I; Patricia Medina A; Sandra Valderrama; Sandra Gualtero T (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2014)
Shunt nephritis is a rare complication associated with the use of atrialventricular shunts and their chronic infection. The microorganisms that cause the infection are generally of low virulence, but they can produce long term infections that permit the production of immune complex that deposit in the kidneys leading to nephritis. Because of this we want to describe the case of an adolescent patient with hydrocephalus, as a consequence of meningitis in the childhood, and chronic use of atrialventricular shunts. She presented fever and child for a long time, these symptoms were secondary to infection of the device, and shunt nephritis was also present.